Evidence Supporting the Diethylstilbestrol Induction of Endometriosis Via Immune-Inflammatory Pathway in Rat Model: Life Sciences-Reproductive Biology - Priya Krishnamoorthy, Sathiya; Balamuthu, Kadalmani (International Journal of Life Science and Pharma Research, 2022)
Endometriosis is a benign reproductive disorder distinguished by chronic inflammation and anomalous progress of stromal cells and glands outside the uterus. Though the etiology of endometriosis is still a matter of debate, the immuneinflammatory mediators are thought to play a major role. Macrophage infiltration and proinflammatory intermediaries in the peritoneal environment peritoneal milieu impact ovarian, uterine function and pelvic morphology, resulting in endometriosis symptoms and signs. The endometriosis model system was developed using diethylstilbestrol (DES) which is examined to develop the disease via the immune-inflammatory pathway. The immune-inflammatory markers (NFKB, MAPK, TNF-α, IL-6 and STAT- 3) were investigated in this study. The results demonstrated that the DES induced endometriosis animal model had a higher level of CA-125, a biomarker of endometriosis. Endometriosis-induced groups had increased levels of NFKB, MAPK, TNF-α, IL-6 and STAT-3 which clearly depicts the immune-inflammatory role in the induction. Finally, the results conclude that DES induced endometriosis via the immune-inflammatory pathway.